2002
DOI: 10.2322/jjsass.50.204
|View full text |Cite
|
Sign up to set email alerts
|

Ignition Characteristics of GH2/GOx Mixture Using a Laser Ablation Ignition.

Abstract: : Irradiating a nano-second laser pulse on a solid surface, a GH2/GO2 combustion chamber was operated to measure the minimum ignition energy for three parameters: the spot diameter, the thruster pressure, and the target material. It was confirmed that this method is useful since the minimum ignition energy can be much less than that of the laser spark ignition. It turned out that the minimum ignition energy increases as the spot diameter increases, and decreases monotonously as the thruster pressure increases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…For usual laser ignition by laser ablation, it has been reported that the critical laser energy density per unit area is independent of the spot diameter. 18) However, the present Trans. Japan Soc.…”
Section: Effects Of Target Position On Critical Energy For Direct Inimentioning
confidence: 47%
See 3 more Smart Citations
“…For usual laser ignition by laser ablation, it has been reported that the critical laser energy density per unit area is independent of the spot diameter. 18) However, the present Trans. Japan Soc.…”
Section: Effects Of Target Position On Critical Energy For Direct Inimentioning
confidence: 47%
“…This result is consistent with the usual ignition characteristics using laser ablation. 18) For ¹2 mm L 4 mm, the critical laser energy increased slightly as L increased, and much larger laser energy was needed for direct initiation in the range of L > 4 mm.…”
Section: Effects Of Target Position On Critical Energy For Direct Inimentioning
confidence: 99%
See 2 more Smart Citations
“…The other is the use of breakdown of the ambient gas by focusing the pulsed-laser beam in the gas. It was clarified that the ablation method needed lower energy than that of the breakdown method 1) . In the other previous works using the ablation method 2,3) , minimum ignition threshold energy of the 10-ns laser pulse of 1064 nm in wavelength from a conventional Q-switched Nd:YAG laser system was 30 μJ with optimal mixture ratio and pressure of gaseous oxygen (GOX) and gaseous hydrogen (GH2).…”
Section: Introductionmentioning
confidence: 99%